Autophagy activation in response to cigarette smoke: Exploring the disparity in laryngeal cancer incidence and outcomes between sexes in South Korea - Min Ji Kim; Jisu Hong; Hyo Won Chang; Yun-Hee Lee; Jun-Pyo Myong; Ah Ra Jung; Yoon Se Lee; Minsu Kwon (Translational Oncology)
Introduction: Laryngeal cancer (LC) presents a significant health challenge globally, with smoking being a major risk factor. Interestingly, LC incidence in females is significantly lower than in males; however, female smokers are more likely to develop Reinke edema (RE) than LC. This study sought to investigate whether autophagy, a major mechanism for RE development, acts as a defense mechanism in laryngeal tissue against cigarette exposure and suppresses LC development in females who smoke. Methods: This study analyzed the National Health Insurance Service (NHIS) data of South Korea to explore sex differences in LC incidence and clinical outcomes. Protein expression was compared between tissues from LC and RE patients. The changes in autophagy-related markers were analyzed after exposure to human vocal fold fibroblast (hVFF) and cigarette smoke extract (CSE). In addition, to explore the relationship between the level of autophagy-related gene expression and clinical features, female LC patients were compared with male patients through an analysis of data from The Cancer Genome Atlas (TCGA). Results: In the NHIS data analyses, male LC patients had an 11 times higher incidence than female patients, even after adjusting for smoking and age. Additionally, female LC patients had significantly better survival rates. RE tissues exhibited increased autophagy-related protein expression compared with LC tissues. hVFFs after CSE exposure demonstrated elevated autophagy markers along with protein expression similar to RE tissue, suggesting autophagy's role in RE development over LC. The TCGA data analysis did not find a significant difference in autophagy-related gene expression, which would explain the favorable female clinical outcomes, between male and female LC patients. Conclusions: This study implies autophagy activation by cigarette smoke is a crucial mechanism for lower LC incidence and better outcomes in females, highlighting the potential for autophagy-targeted LC prevention and treatment strategies.